Pemanfaatan Sistem Monitoring Kualitas Air Berbasis Jarak Jauh Di Pokdakan Mikro Bio Ebi, Kota Pangkalpinang, Bangka Belitung - Mu’alimah Hudatwi; La Ode Wahidin; Aditya Pamungkas; Irma Akhrianti; Eva Utami; Umroh Umroh; Agung Priyambada; Ahmad Fahrul Syarif; Jeanne Darc. N. Manik; Fika Dewi Pratiwi (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The industrial revolution 4.0 has begun to develop in aquaculture activities by utilizing the internet of things (IoT) in the last decade. The increase in intensive shrimp farming on Bangka Island in recent years is still conventional witfar from the use of digital and internet-based technology, especially vaname shrimp farming, including the Bio Ebi Micro Pokdakan in Air Mawar Village. This activity aims to design a water quality monitoring system that can be used in vaname shrimp aquaculture ponds. The main components in designing a remote-based pond water quality monitoring system consist of sensors, processing, data transmission, data storage and display. The activity has started with the design of a water quality monitoring tool in October - November 2022 in the Instrumentation and Acoustics Section of the Marine Science Laboratory at Bangka Belitung University which is then used by partners to monitor water quality conditions in shrimp ponds at Pokdakan Mikro Bio Ebi partners